A Novel 7-Single Nucleotide Polymorphism-Based Clonotyping Test Allows Rapid Prediction of Antimicrobial Susceptibility of Extraintestinal Escherichia coli Directly From Urine Specimens. (18th January 2016) - Tchesnokova, Veronika; Avagyan, Hovhannes; Billig, Mariya; Chattopadhyay, Sujay; Aprikian, Pavel; Chan, Diana; Pseunova, Julietta; Rechkina, Elena; Riddell, Kim; Scholes, Delia; Fang, Ferric C.; Johnson, James R.; et al.
Abstract : This prospective study of cellulitis identified β-hemolytic streptococci as the dominating cause in all investigated subgroups. Group C/G streptococci were more frequently detected than group A streptococci. No single clinical feature substantially increased the probability of confirmed streptococcal etiology. Abstract: Background. Escherichia coli is a highly clonal pathogen. Extraintestinal isolates belong to a limited number of genetically related groups, which often exhibit characteristic antimicrobial resistance profiles. Methods. We developed a rapid clonotyping method for extraintestinal E coli based on detection of the presence or absence of 7 single nucleotide polymorphisms (SNPs) within 2 genes ( fumC and fimH ). A reference set of 2559 E coli isolates, primarily of urinary origin, was used to predict the resolving power of the 7-SNP-based typing method, and 582 representative strains from this set were used to evaluate test robustness. Results. Fifty-four unique SNP combinations ("septatypes") were identified in the reference strains. These septatypes yielded a clonal group resolution power on par with that of traditional multilocus sequence typing. In 72% of isolates, septatype identity predicted sequence type identity with at least 90% (mean, 97%) accuracy. Most septatypes exhibited highly distinctive antimicrobial susceptibility profiles. The 7-SNP-based test could be performed with high specificity and sensitivity using single or multiplex conventional polymerase chain reaction (PCR) and quantitative PCR. In the latter format, E coli presence and septatype identity were determined directly in urine specimens within 45 minutes with bacterial loads as low as 10 2 colony-forming units/mL and, at clinically significant bacterial loads, with 100% sensitivity and specificity. Conclusions. 7-SNP-based typing of E coli can be used for both epidemiological studies and clinical diagnostics, which could greatly improve the empirical selection of antimicrobial therapy.